Studi Komparasi Lingkungan Kerja Karyawan Di Lingkungan Kota Semarang serta Pengaruhnya terhadap Kinerja Karyawan - Firman Aji Sasongko; Bulan Prabawani; Sari Listyorini (Jurnal Ilmu Administrasi Bisnis, 2015)
In the city of Semarang, there are two great and long herbal  company. The successed of the two companies to survived until now because of supported by profesional employees,  in the creation of professional employee must be supported with a comfortable working environment, this research aimed to compare the better and comfortable working environment  feel of employees between njonja Meneer and Jamu Jago and see the effect of the environment work on the performance of each company. To know the problems of the working environment on the object of the study, the researchers took the observations. the type of research is exploratory with comparative studies. The sample of this research are 46 respondents in each companie, using non-probability sampling technique with purposive sampling approach. The method used the quantitative analysis, consists of the average analysis, independent sample t test, multiple linear regression analysis with SPSS for windows version 20.0. This research concluded that the differences in work environment are the physical and non-physical between Njonja Meneer and Jamu Jago and the positive influence of physical work environment and non-physical in Njonja Meneer and Jamu Jago